1991
DOI: 10.1128/mcb.11.1.370
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, nucleotide sequence analysis, and disruption of the MDH2 gene from Saccharomyces cerevisiae: evidence for three isozymes of yeast malate dehydrogenase.

Abstract: The major nonmitochondrial isozyme of malate dehydrogenase (MDH2) in Saccharomyces cerevisiae cells grown with acetate as a carbon source was purified and shown by sodium dodecyl sulfate-polyacrylamide gel electrophoresis to have a subunit molecular weight of approximately 42,000. Enzyme assays and an antiserum prepared against the purified protein were used to screen a collection of acetate-nonutilizing (acetate-) yeast mutants, resulting in identification of mutants in one complementation group that lack act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(76 citation statements)
references
References 54 publications
4
72
0
Order By: Relevance
“…It thus appears that the succinate dehydrogenase complex (SDHC), a tetramer of Sdh1, Sdh2, Sdh3 and Sdh4 (Lombardo et al, 1990;Chapman et al, 1992;Bullis and Lemire, 1994;Daignan-Fornier et al, 1994), is the only TCA cycle-specific enzyme required for acetate utilization on YNBA. Our results also show that the enzymes involved in the glyoxylate cycle operation, such as ACO (Aco1) (Gangloff et al, 1990), malate synthase (Mls1) (Hartig et al, 1992;Kunze et al, 2002), isocitrate lyase (Icl1) (Fernandez et al, 1992;Taylor et al, 1996) and Mdh2 (Minard and McAlister-Henn, 1991), are indispensable for the growth of yeast cells with acetate on YNBA, regardless of their involvement in the TCA cycle. Considering that both the cytoplasmic and mitochondrial isoforms of fumarase (FUM) are encoded by a single gene, FUM1 (Wu and Tzagoloff, 1987), and that operation of the TCA cycle is dispensable on YNBA, as shown above, it is suggested that conversion of fumarate to malate Figure 6.…”
Section: Succinate-fumarate Carrier (Sfc1) Is Essential For Acetate Usupporting
confidence: 54%
See 2 more Smart Citations
“…It thus appears that the succinate dehydrogenase complex (SDHC), a tetramer of Sdh1, Sdh2, Sdh3 and Sdh4 (Lombardo et al, 1990;Chapman et al, 1992;Bullis and Lemire, 1994;Daignan-Fornier et al, 1994), is the only TCA cycle-specific enzyme required for acetate utilization on YNBA. Our results also show that the enzymes involved in the glyoxylate cycle operation, such as ACO (Aco1) (Gangloff et al, 1990), malate synthase (Mls1) (Hartig et al, 1992;Kunze et al, 2002), isocitrate lyase (Icl1) (Fernandez et al, 1992;Taylor et al, 1996) and Mdh2 (Minard and McAlister-Henn, 1991), are indispensable for the growth of yeast cells with acetate on YNBA, regardless of their involvement in the TCA cycle. Considering that both the cytoplasmic and mitochondrial isoforms of fumarase (FUM) are encoded by a single gene, FUM1 (Wu and Tzagoloff, 1987), and that operation of the TCA cycle is dispensable on YNBA, as shown above, it is suggested that conversion of fumarate to malate Figure 6.…”
Section: Succinate-fumarate Carrier (Sfc1) Is Essential For Acetate Usupporting
confidence: 54%
“…In previous studies, the enzyme isoforms of the TCA or glyoxylate cycle have been studied mainly in terms of the correlation between their subcellular distributions and metabolic functions. Three MDH genes, MDH1 (McAlister-Henn and Thompson, 1987), MDH2 (Minard and McAlister-Henn, 1991) and MDH3 (Steffan and McAlister-Henn, 1992), encoding mitochondrial, cytosolic and peroxisomal variants, have been identified in S. cerevisiae. The cytosolic isozyme Mdh2, but not the peroxisomal enzyme Mdh3, functions in the glyoxylate cycle (Minard and McAlister-Henn, 1991;Van Roermund et al, 1995), whereas the mitochondrial isoform Mdh1 participates in the TCA cycle (McAlister-Henn and Thompson, 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A phylogenetic tree was constructed by using the program PILEUP. The following complete MDH amino acid sequences were available: maize (Metzler et al, 1989); sorghum (Luchetta et al, 1991); pig (c) (Birktoft et al, 1989b); mouse (c) (Setoyama et al, 1988); T. fluvus (Nishiyama et al, 1986); S. typhimurium (Lu & Abdelal, 1993); E. coli (McAlister-Henn et al, MDHs (Grant et al, 1987); pig (m) (Birktoft & Banaszak, 1987); mouse (m) (Takeshima et al, 1988); rat (m) 1984); watermelon (Gietl et al, 1990); yeast (Minard & McAlister-Henn, 1991); H. marismortui (Cendrin et al, 1993). The LDH sequences used were rabbit chain" (Sass et al, 1989) and dogfish chain" (Eventoff et al ., 1977) and B. stearothermophilus LDH (Barstow et al, 1986 …”
Section: Three-dimensional Structurementioning
confidence: 99%
“…The sequences of both the mouse and yeast c-and mMDH genes have been reported (Minard and McAlister-Henn, 1991;Setoyama et al, 1988;Takeshima et al, 1988;Thompson et al, 1988). MDH genes have also been isolated from several bacterial sources (McAlister-Henn et al, 1987;Nicholls et al, 1990;Nishiyama et al, 1986).…”
Section: Introductionmentioning
confidence: 99%